Extracellular biosynthesis of silver nanoparticles using the cell-free filtrate of nematophagous fungus Duddingtonia flagrans - Costa Silva LP (Dove Medical Press, 2017)
Laryssa Pinheiro Costa Silva,1 Jairo Pinto Oliveira,2 Wanderson Juvencio Keijok,2 André Romero da Silva,3 Anderson Rocha Aguiar,1 Marco Cesar Cunegundes Guimarães,2 Carolina Magri Ferraz,1 Jackson Victor Araújo,4 Fernando Luiz Tobias,5 Fábio Ribeiro Braga1 1Department of Parasitology, University Vila Velha, Vila Velha, Espírito Santo, Brazil; 2Morphology Department, Federal University of Espírito Santo, Vitória, Espírito Santo, Brazil; 3Federal Institute of Education, Science and Technology of Espírito Santo, Aracruz, Espírito Santo, Brazil; 4Department of Veterinary Medicine, Federal University of Viçosa, Viçosa, Minas Gerais, Brazil; 5Department of Microbiology, University Vila Velha, Vila Velha, Espírito Santo, Brazil Abstract: The biosynthesis of metallic nanoparticles (NPs) using biological systems such as fungi has evolved to become an important area of nanobiotechnology. Herein, we report for the first time the extracellular synthesis of highly stable silver NPs (AgNPs) using the nematophagous fungus Duddingtonia flagrans (AC001). The fungal cell-free filtrate was analyzed by the Bradford method and 3,5-dinitrosalicylic acid assay and used to synthesize the AgNPs in the presence of a 1 mM AgNO3 solution. They have been characterized by UV–Vis spectroscopy, X-ray diffraction, transmission electron microscopy, dynamic light scattering, Zeta potential measurements, Fourier-transform infrared, and Raman spectroscopes. UV–Vis spectroscopy confirmed bioreduction, while X-ray diffractometry established the crystalline nature of the AgNPs. Dynamic light scattering and transmission electron microscopy images showed approximately 11, 38 nm monodisperse and quasispherical AgNPs. Zeta potential analysis was able to show a considerable stability of AgNPs. The N–H stretches in Fourier-transform infrared spectroscopy indicate the presence of protein molecules. The Raman bands suggest that chitinase was involved in the growth and stabilization of AgNPs, through the coating of the particles. Our results show that the NPs we synthesized have good stability, high yield, and monodispersion. Keywords: silver nanoparticles, green synthesis, nematophagous fungi, Duddingtonia flagrans